Layer-engineered interlayer charge transfer in WSe2/WS2 heterostructures. (8th March 2023) - Bian, Ang; Liu, Shuangyan; Zhang, Xiaoxian; Liu, Zeng; He, Dawei; Zhao, Hui; Dai, Jun
Abstract: The layer thickness determines the electronic structure of two-dimensional (2D) materials, leading to different band alignments, which are crucial for the transition metal dichalcogenides heterostructures. Here, we investigated the heterostructure of WSe2 /WS2 with different layer thicknesses by steady-state and transient absorption spectroscopy. We observed different ultrafast charge transfer behaviors in 1L-WSe2 /2L-WS2 and 2L-WSe2 /2L-WS2 few-layer heterostructures. We demonstrate that the layer thickness determines the sequence of intralayer exciton relaxation and interlayer charge transfer. The valley transfer of the band edge induced by the layer thickness can effectively mediate the hot carrier transfer time and interlayer exciton lifetime. These provide us a deeper understanding of carrier dynamics in 2D indirect bandgap semiconductor heterostructures.